2020
DOI: 10.3390/molecules25112640
|View full text |Cite
|
Sign up to set email alerts
|

The Intriguing Effects of Substituents in the N-Phenethyl Moiety of Norhydromorphone: A Bifunctional Opioid from a Set of “Tail Wags Dog” Experiments

Abstract: (−)-N-Phenethyl analogs of optically pure N-norhydromorphone were synthesized and pharmacologically evaluated in several in vitro assays (opioid receptor binding, stimulation of [35S]GTPγS binding, forskolin-induced cAMP accumulation assay, and MOR-mediated β-arrestin recruitment assays). “Body” and “tail” interactions with opioid receptors (a subset of Portoghese’s message-address theory) were used for molecular modeling and simulations, where the “address” can be considered the “body” of the hydromorphone mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Ventilation measures were assessed as described previously [ 25 ]. Briefly, squirrel monkeys were acclimated to a customized acrylic chamber (10″ d × 10″ w × 10″ h) that served as a whole-body plethysmograph (EMKA Technologies, Montreal, PQ, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Ventilation measures were assessed as described previously [ 25 ]. Briefly, squirrel monkeys were acclimated to a customized acrylic chamber (10″ d × 10″ w × 10″ h) that served as a whole-body plethysmograph (EMKA Technologies, Montreal, PQ, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, exchanging the N-methyl group by an N-phenethyl substituent in other opioid ligands, such as 5phenylmorphans, led to MOP antagonists [117,118]. A recent study reported on (-)-Nphenethyl analogs of N-norhydromorphone, with the N-p-chlorophenethylnorhydromor phone as a bifunctional MOP/DOP ligand with partial agonism at the MOP receptor and a full agonism at the DOP receptor, and antinociceptive efficacy without respiratory depression in squirrel monkeys after s.c. administration [119]. Remarkable SAR observations were made for N-methyl substituted 2 and 4 and their N-phenethyl substituted counterparts 2b and 4b, and also extended to the N-phenethyl analogues of morphine and oxymorphone, 22b and 1b, respectively (Figure 3) [94].…”
Section: Modifications In Position 17 Of N-methylmorphinan-6-ones: Design Synthesis and Sar Studiesmentioning
confidence: 82%
“…Furthermore, exchanging the N -methyl group by an N -phenethyl substituent in other opioid ligands, such as 5-phenylmorphans, led to MOP antagonists [ 117 , 118 ]. A recent study reported on (-)- N -phenethyl analogs of N -norhydromorphone, with the N - p -chlorophenethylnorhydromorphone as a bifunctional MOP/DOP ligand with partial agonism at the MOP receptor and a full agonism at the DOP receptor, and antinociceptive efficacy without respiratory depression in squirrel monkeys after s.c. administration [ 119 ].…”
Section: Modifications In Position 17 Of N -Methylmorphinan-6-ones: Design Synthesis and Sar Studiesmentioning
confidence: 99%
“…The crude mixture was loaded onto silica and purified via flash chromatography eluting with 0-30% ethyl acetate in hexane to yield 17 as a yellow oil (3.39 g, 55%) [α] D 25 −33.8 • (c 1.4, CHCl 3 ). 1 H-NMR (400 MHz; CDCl 3 ): δ 7.30-7.26 (m, 1H), 6.81-6.77 (m, 3H), 4.39-4.09 (m, 2H), 3.80 (s, 3H), 3.21-3.14 (m, 1H), 2.65-2.48 (m, 2H), 2.39-2.27 (m, 2H), 2.23-2.14 (m, 2H), 1.80-1.64 (m, 2H), 1.49 (s, 9H); 13 (18). To dry tetrahydrofuran (10 mL) was added sodium hydride (275 mg, 60% weight, 3.0 equiv, 6.87 mmol), followed by slow addition of ethyl 2-(diethoxyphosphoryl)acetate (1.540 g, 1.36 mL, 3.0 equiv., 6.87 mmol).…”
Section: Synthesismentioning
confidence: 99%